(untitled) (Jurnal Simki Postgraduate, 2024)
The aim of this research is to describe the analysis of students’ success factors in solving math story problems on class 3 fractions at SDN 1 Wajak Lor. This type of research is descriptive qualitative with a case study approach. Data collection in this research used tests, observation, and documentation. The researcher used data analysis techniques in the form of data reduction, data presentation, and data verification. Based on the results of data obtained through tests carried out on 3rd-grade students at SDN 1 Wajak Lor with a total of 20 students, it can be seen that the factors for student success are the level of student honesty, motivation, and interest. high student learning in learning, apart from that the student success factor is supported by the student’s readiness in the process of receiving education. Apart from that the student success factor is supported by the student’s readiness in the process of receiving learning.